A construção das identidades dos alunos na educação virtual: uma experiência de EAD no laboratório de pesquisa multimeios na Universidade Federal do Ceará - Young, Regina Santos (2008)
Digital technology has brought about the development of new educational practices, enabling the students to Interact, as opposed to merely receiving instructive materials. Given this scenario, we attempt to understand how students create their online identities, as we believe that emphasizing these identities encourages the discussion debate of diversity, with the objective of discussing the individuality of the participating students, a topic not given due consideration in the curriculum. Other aspects of teaching are also emphasized, besides the/those traditional ones relating to techniques and methods, as questions relating to identity are affected by problems of power and ideology which comprise human relationships a micro and macro social level. Research was conducted during the second semester of 2007 as part of a course given the college of education, at the Federal University of Ceará. Was observed that the identities of the online students consisted of personal and professional information specifically selected and presented by the same, as well as an expression of values and attitudes such as the search for interaction, a willingness to listen to others, isolation, aggressiveness, empathy, etc. The selection information, as well as the attitudes and values are expressed predominantly, in whiting. Nevertheless, the online identities are directly influenced by the social environment, which, in this case, is basically similar to the institutional identity found in traditional education. Of the aforementioned categories (educational strategies, interaction, language, and learning environment), among the participants as being of fundamental importance in the development of their online identities. Nevertheless, we cannot disregard the other categories, as theses complement and blend into the educational dynamics. This is due to the understanding that identities exist only because they are different.